Pendampingan Pendidikan Inklusi Untuk Guru PAUD pada Taman Kanak-Kanak Aisyiyah - Arie Martuty; Fadhilah Latief; Musfira Musfira; Sri Sufliati Romba (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
This community service activity aims to improve the knowledge and skills of Aisyiyah Kindergarten teachers in developing their potential and professional competence related to the implementation of inclusive education. Inclusive education requires teachers to have a sufficient understanding of the characteristics of children with special needs (ABK) and the ability to manage diverse students in the classroom. This activity was implemented in the form of systematically designed and applicable workshops and seminars. The training materials covered four main components: recognizing the characteristics of children with special needs, the concepts and principles of inclusive education, curriculum accommodations and assessments in inclusive classrooms, and techniques for identifying and evaluating learning for children with special needs. The results of the activity showed a significant increase in teachers' understanding and skills in managing inclusive classrooms, particularly in developing Individual Learning Plans (ILPs) tailored to the needs of the children. Teachers also became more confident in implementing adaptive and responsive learning strategies to the diversity of students. However, the sustainability of the program still faces several challenges, including limited supporting resources and minimal parental involvement and support. Therefore, ongoing synergy between schools, parents, and other stakeholders is needed to support the optimal implementation of inclusive education.